Sarcopenic obesity is significantly associated with poorer overall survival after liver transplantation: a systematic review and meta-analysis - Huang, Hui-Bin; Zhu, Yi-Bing; Yu, Da-Xing (Frontiers in Nutrition, 2024)
Background Sarcopenia has been shown to worsen survival after liver transplantation. However, it remains unclear whether coexisting sarcopenia and obesity, so-called sarcopenic obesity (SO), may also synergistically increase their adverse effects. This meta-analysis aimed to evaluate whether pre-transplant SO independently predicts survival in this population. Methods We conducted this study according to the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. The PubMed, Embase, Web of Science, Wanfang, CNKI, and Cochrane databases were searched up to 15 October 2023, for studies with any study design evaluating the relationship between SO and post-transplant survival in patients undergoing liver transplantation. We used ROBINS-E to assess the study quality. The primary outcome was all-cause mortality at any length of follow-up. We calculated pooled odds risks (ORs) or hazard risks (HRs) with 95% confidence intervals (CIs). Heterogeneity was quantified with I2 statistics. Subgroup analyses and publication bias evaluations were also conducted. Results We included nine cohort studies with 2,416 patients. These studies were moderate to high quality. Pre-liver transplant patients commonly experience SO, with a mean prevalence as high as 34%. Overall, patients with SO exhibited a significantly higher overall mortality than patients without SO, as demonstrated by pooled studies using both univariate analysis [HR = 1.76, 95%C 1.33–2.33, p < 0.0001] and multivariate analysis (HR = 2.33, 95%CI 1.34–4.04, p = 0.003). Similar results were also found when comparing patients with or without SO at 1, 3, and 5 years of follow-up (OR = 1.86, 95%CI 1.22–2.83; OR = 1.83, 95%CI: 1.27–2.64; and OR = 1.54, 95% CI 1.02–2.34, respectively). In addition, subgroup analysis based on studies that reported HRs of both sarcopenia and SO indicated both had independent negative effects on post-transplant survival. Conclusion Our meta-analysis showed that SO occurs frequently in liver transplant patients. SO is associated with an increased risk of mortality in such patient populations. Systematic review registration https://doi.org/10.37766/inplasy2024.2.0069 [inplasy2024.2.0069].